The digital economy and urban carbon emissions: mediating effects of green innovation and moderating effects of government intervention - Xiaolong Wu; Zhuo Wu (Frontiers in Environmental Science)
While the digital economy offers a potential pathway toward a low-carbon transition, its net effect on carbon emissions is theoretically ambiguous and the underlying mechanisms remain underexplored. This study investigates the impact of the digital economy on urban carbon emissions by developing a more comprehensive analytical framework that distinguishes between the quantity and quality of green technological innovation as mediating pathways and considers the nonlinear moderating role of government intervention. Using panel data from 285 Chinese cities from 2013 to 2021, we find that the digital economy significantly curbs urban carbon emissions. This effect is mediated by both the quantity and quality of green technological innovation. Crucially, government intervention exhibits a nonlinear, ‘inverted U-shaped’ moderating effect, whereby it initially enhances the digital economy’s emission reduction impact before attenuating it at higher levels of intervention. Further, a heterogeneity analysis reveals that the emission reduction effect is more pronounced in western regions and resource-based cities. Our findings clarify the complex channels linking digitalization to decarbonization and highlight the critical need for carefully calibrated government policies to maximize the environmental benefits of the digital economy.